Efficacy and safety of valsartan in hypertensive children 6 months to 5 years of age - Schaefer, Franz; Coppo, Rosanna; Bagga, Arvind; Senguttuvan, Prabha; Schlosshauer, Rolf; Zhang, Ying; Kadwa, Mahomed (Journal of hypertension, 2013)
Objective: To evaluate a dose-dependent reduction in blood pressure (BP) and overall safety of valsartan in hypertensive children. Method: In a multicenter, randomized, double-blind, parallel-group study, 75 patients with a documented history of hypertension were randomized (2 : 1 : 2) to receive valsartan (0.25, 1 or 4 mg/kg per day) for 6 weeks, then rerandomized (1 : 1) to receive placebo or valsartan for 2 weeks. This followed the 18-week extension study in which all patients received open-label valsartan (1 mg/kg initial dose, titratable up to 4 mg/kg). The primary endpoint was the slope analysis of the dose-response curve for mean sitting SBP (MSSBP) derived through MSSBP reduction over the first 6 weeks. Safety was assessed in terms of adverse events and serious adverse events (SAEs). Results: At Week 6, significant reductions in MSSBP (P < 0.05) from baseline were observed for all three valsartan doses. Greater reductions were observed with the medium and high doses, although the dose-response trend was not statistically significant (P = 0.099). At Week 8, a greater increase in BP was observed in patients who switched from valsartan to placebo; the difference was not significant. At the extension endpoint, MSSBP was comparable to that observed at Week 6 of the core study. Overall, valsartan was well tolerated with no dose-dependent increase in adverse events during the dose-ranging period (Week 0-6) and a comparable incidence of adverse events to placebo during the placebo withdrawal period (Week 7-8). Conclusion: Although a dose-response trend was observed, statistical significance was not achieved during the dose ranging (primary endpoint) or the placebo-withdrawal periods of the study. However, valsartan demonstrated significant reductions in BP compared with baseline and provided consistent reductions over 26 weeks.